From 4QMMT to resurrection : mélanges qumraniens en hommage à Émile Puech - Puech, Emile.; García Martínez, Florentino.; Steudel, Annette.; Tigchelaar, Eibert J. C. (Studies on the Texts of the Desert of Judah, 2006)
This volume consists of nineteen essays, written by internationally renowned scholars such as George Brooke, John Collins, Heinz-Josef Fabry, André Lemaire, Julio Trebolle, Emanuel Tov, James VanderKam and others, presented to Émile Puech, palaeographer and Dead Sea Scrolls specialist, on the occasion of his 65th birthday. All contributions deal with aspects of the Dead Sea Scrolls, including fundamental essays on 4QMMT by Steudel, Kratz and Berthelot, and two papers on resurrection and afterlife. Other essays are concerned with textual criticism and the Hebrew Bible, the Astronomical Enoch, the Admonitions of Qahat, 4QInstruction, and Isaac in the Scrolls. This volume will be indispensable for scholars of the Dead Sea Scrolls, and of interest for scholars of Bible and Second Temple Judaism.